2012
DOI: 10.1073/pnas.1204081109
|View full text |Cite
|
Sign up to set email alerts
|

Role of phosphorylation of Cdc20 in p31 comet -stimulated disassembly of the mitotic checkpoint complex

Abstract: The mitotic checkpoint system delays anaphase until all chromosomes are correctly attached to the mitotic spindle. When the checkpoint is turned on, it promotes the formation of the mitotic checkpoint complex (MCC), which inhibits the ubiquitin ligase anaphase-promoting complex/cyclosome (APC/C). MCC is composed of the checkpoint proteins BubR1, Bub3, and Mad2 bound to the APC/C activator Cdc20. When the checkpoint is satisfied, MCC is disassembled and APC/C becomes active. Previous studies have shown that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 33 publications
1
31
0
Order By: Relevance
“…p31 comet inactivates the mitotic checkpoint in vivo and in vitro in a manner that requires its interaction with Mad2 (12,14). We found that p31 comet stimulates the phosphorylation of Cdc20 in MCC by cyclin-dependent kinase (Cdk), a process that promotes MCC disassembly (15). However, this explained only a part of ATP requirement for p31 comet action: We noted the existence of an additional pathway of MCC disassembly that required p31 comet and ATP, but not phosphorylation (15).…”
mentioning
confidence: 75%
See 4 more Smart Citations
“…p31 comet inactivates the mitotic checkpoint in vivo and in vitro in a manner that requires its interaction with Mad2 (12,14). We found that p31 comet stimulates the phosphorylation of Cdc20 in MCC by cyclin-dependent kinase (Cdk), a process that promotes MCC disassembly (15). However, this explained only a part of ATP requirement for p31 comet action: We noted the existence of an additional pathway of MCC disassembly that required p31 comet and ATP, but not phosphorylation (15).…”
mentioning
confidence: 75%
“…To generate Cdc20-Mad2 substrate for the assay, we used the subcomplex released from immunopurified MCC by incubation with p31 comet , ATP, and Cdk, as described (10,15). The disassembly of Cdc20-Mad2 was determined by immunoprecipitation with anti-Cdc20, followed by immunoblotting for Mad2.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations